Incorporating Lightweight Brick Waste as a Filler Alternative in Asphalt Concrete Wearing Course (AC-WC) Mixtures - Aulia Muttaqin; Nura Safitri; Anwar Efendy; Titik Wahyuningsih (Syntax Literate, 2026)
In Indonesia, many infrastructure development projects are underway, particularly in the transportation sector, including roads and bridges. Road construction typically uses a variety of materials, with asphalt functioning as the binder, while pavement layers often rely on non-renewable resources. This study investigated the effect of incorporating lightweight brick as filler on the properties of AC-WC mixtures. Test specimens were prepared using an Optimum Asphalt Content (OAC) of 6% and varying proportions of cement (S) and lightweight brick (BR) as fillers: 1% S: 0% BR, 0.25% S: 0.75% BR, 0.50% S: 0.50% BR, 0.75% S: 0.25% BR, and 0% S: 1% BR. The Marshall test was conducted to evaluate key parameters, including flow, stability, Marshall Quotient (MQ), Voids in Mix (VIM), Voids Filled with Asphalt (VFA), and Voids in Mineral Aggregate (VMA). The results indicated that the highest stability was achieved in the first variation (1% S: 0% BR) at 1,315 kg, whereas the lowest stability occurred in the fifth variation (0% S: 1% BR) at 1,191 kg. Flow values for all mixtures met specification requirements, ranging from 2 mm to 4 mm. VIM values were within the standard range of 3%–5%. The highest VMA was observed in the fifth variation (18.73%), while the lowest was in the first variation (17.83%). All mixtures also met the minimum VFA specification of 65%. These findings demonstrate that lightweight brick waste can be used as a filler in AC-WC mixtures without compromising the mixture’s quality, making it a viable and sustainable alternative in asphalt concrete production.